Teacher Communication Ability in Supporting Art Achievement of Students with Disability - Muhammad Rasyid Anwar; Agustina Multi Purnomo (LPPM Universitas Jambi, 2021)
The education of students with disabilities has been the focus worldwide since the 1960s. The Indonesian government organizes special schools as a particular means of educating students with disabilities. Communication is part of the educational process that affects children's disabilities, and the teacher's communication skills play an essential role in the education of students with disabilities. This study examined teachers' communication skills in supporting students with disabilities in the arts. The study used a qualitative method with eight teachers, five parents, and ten students. The research was complemented by observations and document studies at SLB Fitria, an SLB with achievements in the arts. The study found that the teacher's communication abilities in teaching students with disabilities include the ability to communicate flexibly using various ways appropriate to the personal conditions and conditions of students' disabilities and the ability to encourage and motivate students to be involved and perform well. The study found that other factors support the artistic achievement of students with disabilities and the teacher's communication skills, namely parental support and the learning system in school. This study suggests paying particular attention to the teacher's communication skills in teaching. The teacher's communication abilities have overcome other shortcomings in their resources (educational background), school shortages (availability of facilities and infrastructure), and student deficiencies.